Rehabilitasi Fisik Pasca COVID-19 dalam Meningkatkan Kapasitas Fungsi Paru - Latif Hisbulloh; Dewi Irawati (Jurnal Keperawatan Silampari, 2022)
This study aims to see the effectiveness of physical activity rehabilitation in post-covid-19 patients in increasing lung function capacity. The method used is a literature review using a database, namely Google Schooler, Embase, Pubmed, and Clinical Key. The results showed that physical rehabilitation therapy was divided into two. The first is a light physical exercise carried out by doing a Short Physical Performance Battery (SPPB) as a measure of performance (time required to walk 4 meters), balance (standing for 10 seconds with legs), and lower extremity strength (time needed to stand and sit). Five times from the chair). This physical exercise is carried out as long as there are no signs and symptoms of worsening. The second therapy is yoga practice therapy which, in its implementation, can increase concentration and eliminate anxiety. In conclusion, early rehabilitation should be given to post-COVID-19 patients. Individuals with limitations due to restriction or lockdown should receive an exercise program to reduce weakness, sarcopenia, cognitive decline, and depression. Keywords: COVID 19, Lung Function, Physical Rehabilitation